EFFECTIVE ASPECTS OF THE USE OF MODERN METHODS AND TECHNOLOGIES IN CONDUCTING ARCHAEOLOGICAL FIELD RESEARCH (Scientific journal of the Fergana State University, 2024)
The article provides information about the effective aspects of the use of modern and technological methods used in the field of archeology in Uzbekistan, as well as some new programs introduced in this field, as well as the territories and monuments where they are used. Some recommendations and reflections are provided regarding the effectiveness of Locus Map in archaeological fieldwork.